EFFICACY OF MICRONUTRIENT APPLICATION ON POTENTIAL OF BRADYRHIZOBIUM BRADYRHIZOBIUM BRADYRHIZOBIUM IN ENHANCEMENT OF GROWTH AND YIELD OF SOYBEAN - SINGH, MAHENDRA; BEURA, KASTURIKASEN (The Bioscan, 2015)
A field experiment was carried out using Randomized Block Design (RBD) with three replications for two consecutive years to investigate the efficiency of inoculated Bradyrhizobium japonicum (B. japonicum) on the soil nutrient status, growth and yield of soybean. Ten different treatments were taken into consideration which included different levels of micronutrients with and without B. japonicum inoculation. Inoculation with B. japonicum significantly increased the biological and grain yield of soybean over control by 18.1 and 8.83 % respectively. Due to inoculation of B. japonicum along with Zinc@ 5 kg ha1, the biological yield and grain yield gave significantly higher values of 6999.03 and 2775.71 kgha-1 respectively. Application of Molybdenum with B. japonicum inoculation gave a biological yield and grain yield of 6321.4 and 2441.18 kgha-1 respectively. The maximum grain yield, biological yield and straw yield (2789.64 kg ha-1, 7020.60 kg ha-1 and 2426.47 kg ha-1 respectively) were recorded with the treatment B. japonicum + 5 kg Zn ha-1 + 0.5 kg B ha-1 + 4 g Mo kg-1. Thus the inoculation with B. japonicum along with micronutrients improved plant growth, nutrient acquisition and yield.